The effect of the tale-tweaking tool on students’ narrative writing performance - Mohd Amin, Noraziah; Mohamad Marzaini, Anwar Farhan; Abd Rashid, Muhammad Haziq; Mohd Fauzey, Nur Fatin Shahmina; Abdullah, Mohd Firdaus (Academica Press Solutions, 2025)
The Tale-Tweaking Tool (TTT) is a cutting-edge smartphone application designed to enhance the storytelling skills of first-semester diploma students at Universiti Teknologi MARA (UiTM). Students accustomed to academic writing, particularly expository writing, often struggle to compose a concise 100-word narrative paragraph, a requirement of UiTM's new English language curriculum for first-semester diploma students (LCC111). To address these challenges, TTT provides lectures, multiple-choice questions based on the lectures, and step-by-step exercises to develop students’ ability to craft succinct narratives. After engaging with the app, an online survey was conducted to gather feedback on its effectiveness. The survey results indicate that TTT significantly enhanced students’ understanding of sentence construction, story sequencing, concise writing and narrative elements such as plot, character, and setting. In conclusion, TTT serves as a valuable teaching tool that greatly enhances narrative writing skills, making it an essential component of UiTM’s current language curriculum. Its potential for wider adoption and further refinement could revolutionise creative writing instruction, ultimately benefiting a broader audience.